2009
DOI: 10.1152/ajpregu.91006.2008
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal programming of rat thick ascending limb chloride transport by low-protein diet and dexamethasone

Abstract: Dagan A, Habib S, Gattineni J, Dwarakanath V, Baum M. Prenatal programming of rat thick ascending limb chloride transport by low-protein diet and dexamethasone. Am J Physiol Regul Integr Comp Physiol 297: R93-R99, 2009. First published April 29, 2009 doi:10.1152/ajpregu.91006.2008.-Prenatal administration of dexamethasone and a low-protein diet has been shown to result in hypertension in the offspring when they are adults. The cause for the hypertension is unknown. The purpose of this study was to examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 49 publications
3
48
2
Order By: Relevance
“…If the reported increase in NKCC2 in the LP kidney [14][15][16] was associated with greater sodium reabsorption, one might expect to see a reduction in FE Na distal in LP rats infused with AM+BF (i.e., outflow from the TAL). This was not the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the reported increase in NKCC2 in the LP kidney [14][15][16] was associated with greater sodium reabsorption, one might expect to see a reduction in FE Na distal in LP rats infused with AM+BF (i.e., outflow from the TAL). This was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone exposure is associated with an increase in tubular expression of the sodium:hydrogen exchanger type-3 (NHE3 located in the proximal tubule), the bumetanide-sensitive sodium:potassium:chloride (Na + : K + :2Cl -) cotransporter [NKCC2 or BSC1, located in the thick ascending limb (TAL)], and the thiazide-sensitive Na + :Cl -cotransporter (NCC or TSC, located in the distal tubule); however, the amiloride (AM)-sensitive epithelial sodium channel (ENaC, located in the collecting duct) is unaltered [12,13]. In the LP model, NHE-3 and ENaC are unaltered but NKCC2 and, in some reports, NCC are increased [14][15][16]. One group also described increased renal Na + :K + adenosine triphosphatase (ATPase_-α 1 and-β 1 subunit messenger RNA (mRNA) expression in LP rat kidneys [17], whereas we have shown that whole-kidney Na + :K + ATPase pump activity and expression of the α 1 subunit in the inner medulla are reduced markedly [15].…”
Section: Introductionmentioning
confidence: 99%
“…46,47 Finally, previous studies have shown that maternal dietary protein deprivation programs an increase in NKCC2 and NCC in adult offspring and prenatal dexamethasone increases these transporters as well as NHE3. 8,12,14,18 In the previous studies, the mothers were reared by the same mothers administered a low-protein diet or prenatal dexamethasone. As shown in …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Many animal studies have shown that prenatal insults leading to small for gestational age offspring result in hypertension and a reduction in glomerular number when offspring are studied as adults. [4][5][6][7][8][9][10][11][12] The pathogenesis of the hypertension resulting from prenatal insults has been shown to be multifactorial and involves more than just a reduction in nephron number. [12][13][14][15] Factors such as activation of the renin-angiotensin system, an increase in renal sodium transport, and an increase in sympathetic tone may contribute to the hypertension with prenatal programming.…”
Section: Introductionmentioning
confidence: 99%
“…At least four measurements were carried out per period, and the mean of the collections in each period was used to represent the chloride absorption for that period. We have previously demonstrated that passive chloride transport in mTAL is not detectable (11).…”
Section: Animalsmentioning
confidence: 97%